2015
DOI: 10.1124/jpet.114.222356
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Bupropion and 3,4-Methylenedioxymethamphetamine in Healthy Subjects

Abstract: 3,4-Methylenedioxymethamphetamine (MDMA; "ecstasy") is a popular recreational drug. The aim of the present study was to explore the role of dopamine in the psychotropic effects of MDMA using bupropion to inhibit the dopamine and norepinephrine transporters through which MDMA releases dopamine and norepinephrine. The pharmacodynamic and pharmacokinetic interactions between bupropion and MDMA in 16 healthy subjects were investigated using a double-blind, placebo-controlled, crossover design. Bupropion reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 53 publications
3
52
0
1
Order By: Relevance
“…Seven studies each included 16 subjects (total of 112 subjects) who received 125 mg MDMA twice, once alone and once after pretreatment with a medication (Hysek et al, 2012a;Hysek et al, 2012c;Hysek et al, 2012d;Hysek et al, 2011;Hysek and Liechti, 2012;Hysek et al, 2014b;Schmid et al, 2015b). An additional unpublished study included 24 subjects who received 125 mg MDMA once without pretreatment (ClinTrials.gov ID: NCT01951508).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies each included 16 subjects (total of 112 subjects) who received 125 mg MDMA twice, once alone and once after pretreatment with a medication (Hysek et al, 2012a;Hysek et al, 2012c;Hysek et al, 2012d;Hysek et al, 2011;Hysek and Liechti, 2012;Hysek et al, 2014b;Schmid et al, 2015b). An additional unpublished study included 24 subjects who received 125 mg MDMA once without pretreatment (ClinTrials.gov ID: NCT01951508).…”
Section: Methodsmentioning
confidence: 99%
“…This was a pooled analysis of nine Phase I double-blind, placebo-controlled, crossover studies in healthy subjects (Hysek et al, 2012a;Hysek et al, 2012c;Hysek et al, 2012d;Hysek et al, 2011;Hysek and Liechti, 2012;Hysek et al, 2014b;Schmid et al, 2014;Schmid et al, 2015b). These studies were all conducted at the University Hospital Basel and included a total of 166 subjects who were all psychiatrically screened and healthy.…”
Section: Methodsmentioning
confidence: 99%
“…The method was fully validated, including selectivity, recovery, matrix effects, bias and imprecision, stabilities, and limit of quantification (LOQ) and criteria were fulfilled and LOQs sufficient for the expected plasma concentrations of all analytes except for DHMA (Steuer et al, 2015). All blood plasma samples of a previous study (Schmid et al, 2015) were stored at -20°C prior to analysis. Data on stability of MDMA and its phase I metabolites were previously published and no instability could be observed up to 6 months (Clauwaert et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…We used plasma samples from a double-blind, placebo-controlled, crossover study with four experimental test sessions (placebo-placebo, bupropion-placebo, placebo-MDMA, and bupropion-MDMA) that were performed in a counterbalanced order according to a Latin square randomization design as described in detail by Schmid et al (2015). The clinical study was conducted at the University Hospital of Basel in accordance with the Declaration of Helsinki and International Conference on Harmonization Guidelines in Good Clinical Practice and with approval by the Ethics Committee of the Canton of Basel, Switzerland, and the Swiss Agency for Therapeutic Products (Swissmedic).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies that assess pharmacological interactions between a psychostimulant and receptor-selective antagonists or well-characterized transporter ligands shed light on specific molecular target mediating subjective effects and acute toxicity in humans. For example, our laboratory investigated the mode of action of MDMA in humans by blocking the NET, SERT, or DAT or combinations thereof (Hysek et al, 2011;Hysek et al, 2012c;Hysek et al, 2014;Liechti et al, 2000;Schmid et al, 2014;Schmid et al, 2015). These studies showed that NET and α 1 -adrenergic stimulation are crucially involved in MDMA-induced sympathomimetic activation, including elevations of blood pressure and body temperature (Hysek et al, 2012a;Hysek et al, 2013;Hysek et al, 2011;Schmid et al, 2015) and that the SERT-mediated release of 5-HT is involved in the subjective entactogenic/empathogenic effects of MDMA (Hysek et al, 2012b;Hysek et al, 2012c;Liechti et al, 2000).…”
Section: Methods For Studying Transporter and Receptor Pharmacology Imentioning
confidence: 99%